2023
DOI: 10.3390/plants12020327
|View full text |Cite
|
Sign up to set email alerts
|

Cross-School Collaboration to Develop and Implement Self-Construction Greening Systems for Schools

Abstract: The positive effects of green infrastructure in the urban environment are nowadays widely known and proven by research. Yet, greening, which serves to improve the indoor climate and people’s well-being, is integrated very limited in public facilities such as schools. Reasons for this are seen in a lack of knowledge and financing opportunities. A focus, among others, of the MehrGrüneSchulen research project is the interdisciplinary development of cost-effective greening solutions for schools. The designs were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…It was shown that for almost all green infrastructure applications, the operation phase accounts for the highest percentage of costs. To minimize these costs, the maintenance should be performed by the students themselves, which is only possible with low-tech greening systems, as suggested in [36]. To guide interested school representatives to their individual financing options for a low-cost, low-tech greening system, this study proposes a three-step path: 1. define the greening project initiator; 2. clarify the desired green infrastructure; and 3. determine the amount of funding needed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was shown that for almost all green infrastructure applications, the operation phase accounts for the highest percentage of costs. To minimize these costs, the maintenance should be performed by the students themselves, which is only possible with low-tech greening systems, as suggested in [36]. To guide interested school representatives to their individual financing options for a low-cost, low-tech greening system, this study proposes a three-step path: 1. define the greening project initiator; 2. clarify the desired green infrastructure; and 3. determine the amount of funding needed.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the attention was shifted to other greenery systems for schools that could be built and maintained at low costs and without demanding special horticultural or technical knowledge. For this reason, indoor and outdoor lowcost greening systems have been developed that can be built, maintained, and eventually be disposed of by students of secondary schools themselves, as shown in [36]. When calculating the life-cycle costs of the developed low-cost greening systems, two scenarios were used: 1. a minimum-cost scenario, assuming that the maintenance is performed by the students, for example, as part of the biology classes; and 2. a maximum-cost scenario, assuming a maintenance contract with a green care company.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Teichmann et al [ 45 ] published work on the role of schools in the Special Issue. Their more specific topic was cooperation between schools for the development and implementation of schools’ self-constructed greening systems.…”
Section: Landscape Architecture and Green Areas (8 Articles)mentioning
confidence: 99%